Implikasi Sidang Keliling di Pengadilan Agama Majene Kelas II Terhadap Rasa Keadilan Para Pihak (Telaah Maslahah Mursalah) - Fatta, Muh. Irsyad; Kurniati, Kurniati; Talli, Halim; Patimah, Patimah; Asni, Asni (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of this research is to explore the implications of the practice of mobile court at the Majene Religious Court on the sense of justice of the parties, with a focus on studying Maslahah Murlah. The research method used is qualitative with a normative syar'i theological approach and a juridical-empirical approach. Data was collected through observation, interviews, and documentation, then analyzed by data reduction, data presentation, data editing, data analysis, and testing data validity by combining data. The research results show that the mobile court conducted by the Majene Religious Court is in accordance with the Maslahah Murlah concept by helping remote communities, spreading justice evenly, and maximizing services. The stages of the circuit court process include submitting a budget, determining the implementation time, determining the panel of judges, trial, and mediation. The implication of this research is the need for the Majene Religious Court to continue to provide the best service to the community, for the Supreme Court to pay attention to judicial institutions throughout Indonesia, and to find solutions to overcome the negative impacts of mobile courts.